Reproductive health status of women referring to addiction centers - Amir Ali Akbari, Sedgheh; Bahry, Mahnaz; Kariman, Nour al sadat; Alavi Majd, Hamid (Advances in Nursing & Midwifery, 2011)
Abstract Background and aim Addiction to drugs and substance abuse is considered a psychosocial health problem. Its prevalence in women has dramatically increased in the past two decades, who are mostly at reproductive age. The aim of this study was to determine the reproductive health status of women referring to addiction centers at Tehran in 2009. Materials and methods In this descriptive study, 200 addicted women were sequentially selected by a nonrandomized sampling method. A questionnaire with items related to demographic information, drug abuse, obstetrical history, menstruation and family planning was used for data collection. Its validity and reliability were achieved by content and test-retest (r=0.98) methods respectively. Findings Opioid and crack were the most common drugs. 34% of cases had started substance abuse between 14-20 years old. The mean of parities was 2.95±1.83. The outcome of 27.6% of pregnancies was low birth weight with 7% of neonates having physical malformation. 145 women (72.5%) were at reproductive age. 82% had had regular menses before addiction and 91.7% experienced dysmenorrhea in the menstruations. The amount of bleeding and the intervals of cycles had changed after addiction in 45.5% and 33.1% of the subjects respectively. 66.2% of reproductive women with sexual activity used a contraceptive method and withdrawal method was the most common one. Conclusion According to the results, reproductive health status of addicted women is in need of further assessment and supervision. Therefore, it is recommended to attend more to these women by planning appropriate programs to improve reproductive health services for them. Keywords: Reproductive health, Women, Addiction. *Corresponding Author: Sedighe AmirAli Akbari, Lecturer, Dept of Midwifery, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. E-mail: asa_akbari@yahoo.com